Autobiografia di un mondo in declino - Bonanate, Luigi (SocietàMutamentoPolitica, 2011)
International crisis is increasingly deepening as no new international order grew after the bipolarism's fall. Wars dominated XX century and every one of them produced a new strong international order, to which every state was attended to obey. From XVI century on, this was an incremental and unrestrainable historic tendency. After bipolarity's fall, globalization produced no improvement nor order. In the meanwhile too many problems –regarding identity, ethnicity and race, social problems, in a word – became too difficult to control, in the absence of a new order. The world in now in a phase of entropy and is no more able to make the work (in the sense of phisics) necessary to let society survive. Will this new world find the firmness to continue?